2010
DOI: 10.1308/003588410x12518836439083
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and outcome of incidental breast lesions detected by computed tomography

Abstract: INTRODUCTION In the UK, the majority of breast cancers are diagnosed through symptomatic breast clinics and the breast screening programmes. With increased use of computed tomography (CT) to assess various pathologies, breast lesions are picked up incidentally. The aim of this study was to investigate the incidence and outcomes of breast lesions detected incidentally on CT scans. PATIENTS AND METHODS A retrospective study was conducted to assess the incidence and outcome of incidentally found breast lesions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
(9 reference statements)
2
22
0
3
Order By: Relevance
“…In these studies, 24-32% of incidental breast lesions were subsequently proven to be malignant (6-8). Our study showed a much higher rate (70%) of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, 24-32% of incidental breast lesions were subsequently proven to be malignant (6-8). Our study showed a much higher rate (70%) of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Improved imaging approaches combined with core needle biopsies have led to earlier detection of abnormal breast lesions in women over time, with most lesions diagnosed as non-cancerous [13]. Non-cancerous breast lesions are highly variable, and include non-proliferative diseases such as breast cysts, and proliferative diseases such as hyperplasia and intraductal papilloma [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increasing use of MDCT for detection of other pathologies, new breast lesions are being increasingly detected incidentally during CT scans for diseases other than those of the breast (7,8). CT scans are not only sensitive for detection of small breast lesions within dense breasts but also allow for better visualization of some breast lesions adjacent to the chest wall (4,7,9). Usually, chest CT scans are reported by radiologists who do not specialize in breast imaging and pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Several CT techniques have been used in assessment of breast lesions including contrast-enhanced CT scans, multi-detector techniques MDCT, and dual time positron emission tomography-computed tomography (7). For an accurate assessment of breast lesions, standardized terminology is required for descrip- This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation